2015
DOI: 10.1002/jobm.201400783
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous nitrification and denitrification by novel heterotrophs in remediation of fish processing effluent

Abstract: Three isolates viz. Lysinibacillus sp. HT13, Alcaligenes sp. HT15 and Proteus sp. HT37 isolated from fish processing effluent and having a C/N ratio of 2, removed 218, 169, and 400 µg cell(-1) day(-1) NH4(+)-N, respectively without subsequent build up of nitrite or nitrate. Ability of the selected isolates in removing NH4(+)-N, NO2(-)-N, and NO3(-)-N was checked in the presence of four commonly reported and tested effluent carbon sources viz. pyruvate, glycerol, methanol, and acetate. Further, when supplemente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
(43 reference statements)
2
11
0
Order By: Relevance
“…a and d). Planktonic stage had exhibited relatively higher residual nitrite and nitrate presence (reported previously by us in ) than in MBBR stage after 24 h of incubation (Fig. b and c).…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…a and d). Planktonic stage had exhibited relatively higher residual nitrite and nitrate presence (reported previously by us in ) than in MBBR stage after 24 h of incubation (Fig. b and c).…”
Section: Resultssupporting
confidence: 75%
“…The mixed consortium biofilm on carriers showed highest removal of ammonia and lowest production of nitrite and nitrate (p-value, Ã < 0.05) than carriers with individual bacterial biofilms. With respect to the individual remediation capability of the isolates used in planktonic stage (reported previously by us in [8]) and their biofilms on carriers (Fig. 1b), the mixed biofilms exhibited higher denitrification of effluents and minimum residual nitrogenous byproducts.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Similar metabolic activity was displayed by the Proteus sp. strain related to P. mirabilis , isolated from effluents from a fish processing plant in India [86]. Simultaneous aerobic nitrification and denitrification leading to the efficient removal of nitrogen by this heterotrophic bacterium are suggested to be applied in fish waste treatment.…”
Section: Proteus In Bioremediation and Plant Growth Promotionmentioning
confidence: 99%
“…For instance, the genera Ochrobactrum, Agrobacterium and Brevundimonas are known to include nitrogen-fixing species. Sequences related to nitrifiers such as Labrenzia, Bacillus and Lysinibacillus (Mishra et al 2015) and denitrifiers such as Thiobacillus and Pseudomonas (Ruiz-Rueda et al 2009) have also been encountered. Earlier studies have reported the presence of these bacterial taxa (Haaijer et al 2006) and the occurrence of nitrogen cycle processes such as N2 fixation, nitrification and denitrification (Whitmire & Hamilton 2005) in other wetlands.…”
Section: Sulfur and Nitrogen Cycles In The Rhizospehere Soilsmentioning
confidence: 99%